Antimicrobial activity and toxicity of Syzygium australe and Syzygium leuhmannii fruit extracts - Sautron, C.; Cock, I.E. (Pharmacognosy Communications)
Introduction: Many species of Syzygium are known to have antiseptic activity. Several Australian Syzygium species had roles as traditional bush medicines for Australian Aborigines although their antiseptic potential has not been rigorously studied. Methods: The antimicrobial activity of solvent extracts of Syzygium australe and Syzygium leuhmannii fruits were investigated by disc diffusion assay against a panel of bacteria and fungi and their MIC values were determined. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: The methanolic extracts of the fruit of both Syzygium species displayed the greater antibacterial activity of the extracts tested. S. australe generally had greater efficacy than the S. leuhmannii extracts. S. australe and S. leuhmannii fruit methanolic extract inhibited the growth of 13 (93%) and 12 (86%) of the 14 bacteria tested. Gram-positive and Gram-negative bacteria were both susceptible, although a slightly greater susceptibility of Gram-positive bacteria was noted. Nine (90%) and 8 (80%) of the 10 Gram-negative bacteria had their growth inhibited by S. australe and S. leuhmannii fruit methanolic extract extracts respectively. In contrast, methanolic extracts of both species inhibited growth of 100% of the Gram-positive bacteria tested. None of the extracts displayed broad antifungal activity. Indeed, none of the extracts inhibited the growth of A. niger or C. albicans. Only S. cerevisiae growth was affected and then only by the chloroform and hexane extracts. The methanolic, aqueous and ethyl acetate extracts of both Syzygium species were toxic in the Artemia franciscanabioassay, inducing significant mortality at <1000 μg/ml. Conclusions: The inhibitory bioactivity of S. australe against the bacterial panel validate Australian Aboriginal usage of S. australe leaves as antiseptic agents and confirms their medicinal potential, although care is needed in the uses of these extracts for these purposes due to their reported toxicity.
Keywords: Syzygium australe; Syzygium leuhmannii; Australian plants; antibacterial activity; medicinal plants; toxicity